MODEL PERMAINAN BASKET HOLL DALAM PEMBELAJARAN PENJASORKES BOLA BESAR PADA SISWA KELAS VIII SMP NEGERI 1 PURBALINGGA (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
The game of basketball is taught in a standardized form of the game so it's still got students who find it difficultto play this game. Thus the need for modification in the learning process. This research method is thedevelopment of research, and the results of the model developers basket holl development. The analysisprocedure includes product development product that will be developed, developing initial products, expertvalidation and revision, testing and revision small group, large group and test the final product. The data wascollected using field observations and questionnaires were obtained from expert evaluation and the results of thequestionnaires by students. The data analysis technique used is descriptive percentages. From the test resultsobtained by experts the average percentage of product analysis of 84.6% with both criteria. Data results of thestudent questionnaire on a small test group gained an average percentage of 77.22% with the answer to bothcategories, and questionnaire data from a large group of students test answers obtained with the percentage86.42% with both categories. Based on the research data, it was concluded that the game of basketball can beused basket holl teachers as an alternative in learning Penjasorkes game.